Effect of irrigation and fertigation scheduling on input use efficiency, yield and quality of guava cv. Lalit under intensive orcharding system - KUMAWAT, K. L.; SAROLIA, D. K.; KAUSHIK, R. A.; ., RAMNIWAS; DEVRA, N. S. (Journal of Soil and Water Conservation, 2020)
A study was conducted on guava cv. Lalit to find out the effect of irrigation and fertigation scheduling on WUE, FUE, moisture distribution pattern, leaf NPK content and nutrient uptake under intensive orcharding. The experiment consisted of 15 treatments combination comprising three different level of irrigation [50% (I1), 75% (I2) and 100% (I3) irrigation of pan evaporation] and five level of fertigation [20% (F1), 40% (F2), 60% (F3), 80% (F4) and 100% (F5) of recommended dose of NPK. Among the different treatment combination, maximum WUE (1038.50 kg ha-1 cm-1) was recorded under I1F4 treatment combination. Whereas, I3F5 resulted in maximum P content in leaves (0.28%), however, maximum yield plant-1 (6.75 kg), estimated yield ha-1 (33.75 t), uptake of N (652.92 kg ha-1), P (86.15 kg ha-1) and K (425.08 kg ha-1) were obtained under I2F4. Treatment combination I2F3 obtained a maximum net return (Rs. 2, 79,081.08) which was statistically at par with I2F4. Further, maximum B: C ratio (2.64) jointly recorded in I1F1 and I2F1, followed by (2.62) in I3F1. Treatments combination I2F3 and I2F4 were non significant between each other with respect to WUE, NPK uptake, yield tree-1 and estimated yield ha-1. Thus, based on the results of experiment we can conclude that treatment combination I2F3 (75 % irrigation of PE + 60% of recommended dose of NPK) efficiently utilized water and fertilizers in form of yield in guava cv. Lalit under intensive orcharding system.